Controlled evaluation of a transition clinic for Dutch young people with cystic fibrosis. Issue 11 (19th August 2019) - Peeters, Mariëlle A. C.; Sattoe, Jane N. T.; van Staa, AnneLoes; Versteeg, Simone E.; Heeres, Inge; Rutjes, Niels W.; Janssens, Hettie M.
Abstract: Background: Transition clinics (TCs) are advocated as best practice to support young people with cystic fibrosis (CF) during transition to adulthood and adult care. We aimed to research the functioning of a TC for young people with CF compared with direct hand‐over care and to evaluate whether those treated at the TC have better transfer experiences and outcomes compared with the control group. Methods: Mixed‐methods retrospective controlled design, including interviews with professionals, observations of clinics, chart reviews (at four measurement moments), and patient surveys. Qualitative data analysis focused on organization and daily routines, and barriers and facilitators experienced. Young people's transfer experiences, self‐management, health care use, and clinical outcomes were assessed quantitatively. Results: The most notable feature distinguishing the TC and direct hand‐over care comprised joint consultations between pediatric and adult care professionals in the former. A transition coordinator was considered essential for the success of the TC. The main barriers were lack of time, planning, and reimbursement issues. Young people treated at the TC tended to have better transfer experiences and were more satisfied. They reported significantly more trust in their adult care professionals. Their self‐management‐related outcomes were less favorable. Conclusions: The TC had several perceived benefits and showed positive trends in transfer experiences and satisfaction, but no differences in health‐related outcomes. Structured preparation of young people, joint consultations with pediatric and adult care professionals, and better coordination were perceived as facilitating elements. Further improvement demands solutions for organizational and financial barriers, and better embedding of self‐management interventions in CF care.